1997
DOI: 10.1016/s0954-6111(97)90077-9
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar haemorrhage revealing epitheloid haemangioendothelioma

Abstract: Epithelioid haemangioendothelioma of the pulmonary vessels is a rare neoplasm which usually has a minimal clinical expression. The present case report describes an exceptional case with severe inaugural alveolar haemorrhage which led to death by acute respiratory failure within a few weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
2
0
2
Order By: Relevance
“…Moreover, solitary pulmonary nodules and endobronchial lesions were found in 4 cases and 1 case, respectively, which are rarely reported. Unfortunately, the pattern of bilateral multifocal areas of reticulonodular was initially misdiagnosed as diffuse alveolar hemorrhage in 2 cases of our study, as reported in previous studies ( 29 , 30 ). Similarly, the pattern of bilateral multiple pulmonary nodules was misdiagnosed with lung metastases or lung cancer, which is consistent with previous studies ( 31 - 33 ).…”
Section: Discussionsupporting
confidence: 48%
“…Moreover, solitary pulmonary nodules and endobronchial lesions were found in 4 cases and 1 case, respectively, which are rarely reported. Unfortunately, the pattern of bilateral multifocal areas of reticulonodular was initially misdiagnosed as diffuse alveolar hemorrhage in 2 cases of our study, as reported in previous studies ( 29 , 30 ). Similarly, the pattern of bilateral multiple pulmonary nodules was misdiagnosed with lung metastases or lung cancer, which is consistent with previous studies ( 31 - 33 ).…”
Section: Discussionsupporting
confidence: 48%
“…Chest pain, cough and sputum are common as are nonspecific symptoms. Two patients presented with alveolar haemorrhage [28,29] and one with rapidly deteriorating pulmonary hypertension [30].…”
Section: Discussionmentioning
confidence: 99%
“…Ebenso wurde kasuistisch über eine DAH in Assoziati− on mit einer Colitis ulcerosa und einer primär sklerosierenden Cholangitis [107] oder beim M. Crohn berichtet [108]. Eine Rari− tät ist ein Hämangioendotheliom [109,110]. Selten ist eine pul− monale Sarkoidose von einer DAH begleitet [111].…”
Section: äTiologieunclassified
“…Nur selten ist bei Patienten mit einer DAH histologisch der Nachweis spezi− fischer Diagnosen möglich, z. B. bei der Lymphangioleiomyoma− tose, der pulmonalen kapillären Hämangiomatose und bei malignen Erkrankungen [109,124]. Obwohl DAH relativ selten sind, haben sie aufgrund ihres oft schweren, potenziell letalen Verlaufs eine erhebliche klinische Bedeutung.…”
Section: äTiologieunclassified